Smartphone Application on Perioperative Cardiac Surgery: A Systematic Review - Sidik Awaludin; Elly Nurachmah; Dwi Novitasari (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Information technology used in the health sector is known as e-health. Smartphone applications are starting to be widely used for long-term condition monitoring management in the medical and health fields. Perioperative cardiac surgery procedures require long-term monitoring. This study aimed to find out about smartphone use in perioperative cardiac surgery. A systematic review design. The reporting framework uses Featured Reporting Items for Systematic Review and Followed Meta-analysis to report findings. Data Sources, CINAHL, ProQuest, Science Direct, and Google Scholar searched for English-language articles published from January 2010 to August 2020 with the keywords"cardiac surgery," "smartphone," and "peri-operative". Six articles that met the inclusion criteria were the samples analyzed in this study. The instrument used to assess the quality of the study uses the Downs and Black checklist. In the pre-operation stage, a smartphone application has been used for surgical planning, assessment, education, training, diagnosis, telemedicine, navigation, and behavior modification interventions. In the intraoperative stage, smartphones are used for hemodynamic monitoring. In the post-operative stage, smartphones are used for monitoring surgical wounds. The benefits of smartphones in peri-operative cardiac surgery include diagnosis, telemedicine, navigation, and surgical planning, training, data collection, hemodynamic monitoring, nursing intervention media, and surgical wounds. Abstrak: Teknologi informasi yang digunakan dalam bidang kesehatan dikenal dengan istilah e-health. Aplikasi smartphone telah digunakan dalam bidang kedokteran dan kesehatan sebagai alat untuk manajemen pemantauan kondisi jangka panjang. Kondisi perioperatif pada bedah jantung memerlukan monitoring dengan jangka waktu yang panjang. Penelitian ini memiliki tujuan untuk mengetahui penggunaan smartphone pada perioperatif bedah jantung. Desain penelitian ini systematic review. Kerangka kerja dalam pelaporan menggunakan PRISMA untuk melaporkan temuan. Sumber Data ProQuest, Google Scholar, CINAHL, dan Science Direct dicari untuk mengidentifikasi bahasa Inggris asli yang diterbitkan, diterbitkan dari Januari 2010 hingga Agustus 2020 dengan kata kunci "cardiac surgery" "smartphone" dan "perioperatif". Enam artikel memenuhi kriteria inklusi menjadi sampel akhir. Instrumen untuk menilai kualitas studi dinilai menggunakan daftar periksa Downs dan Black. Smartphone digunakan dalam tahap pra operasi seperti diagnosis, telemedicine, navigasi dan perencanaan bedah, pelatihan, pengumpulan data diikuti dengan pendidikan pasien dan intervensi modifikasi perilaku. Pada tahap intraoperatif, smartphone digunakan untuk pemantauan hemodinamik. Pada tahap pasca operasi, smartphone digunakan untuk memantau luka operasi. Manfaat smartphone dalam bedah jantung  antara lain untuk diagnosis, telemedicine, navigasi dan perencanaan bedah, pelatihan, pengumpulan data, pemantauan hemodinamik, median intervensi keperawatan dan pemantauan luka bedah.